Residual impact of arbuscular mycorrhizal fungi and Rhizobium on growth and productivity of pigeon pea (Cajanus cajan (L.) Huth) - Yadava, A K; Sharma, G; Mehta, C M (Plant Science Today, 2026)
A two-year field trial was conducted to examine the residual effects of arbuscular mycorrhizal fungi (AMF) and Rhizobium on the growth and productivity of pigeon pea. The study aimed to clarify how these two biological agents affect plant growth and yield metrics differently. The study was conducted at Lovely Professional University, Phagwara, Kapurthala district, Punjab, during the kharif season 2023–24. The trial tested different doses of recommended dose of fertiliser (RDF), combined with AMF and Rhizobium residues, on pigeon pea. The treatment includes T1 (100 % RDF), T2 (AMF + 100 % RDF), T3 (Rhizobium + 100 % RDF), T4 (AMF + Rhizobium + 100 % RDF), T5 (75 % RDF), T6 Maize (AMF + 75 % RDF), T7 (Rhizobium + 75 % RDF), T8 (AMF + Rhizobium + 75 % RDF), T9 (50 % RDF), T10 (AMF + 50 % RDF), T11(Rhizobium + 50 % RDF) and T12 (AMF + Rhizobium + 50 % RDF). Plant growth and yield attributes were analyzed using standard methods. A significant residual impact of AMF and Rhizobium on plant growth and yield was observed. Compared to the T1, T8 (AMF + Rhizobium + 75 % RDF) increased the chlorophyll index (17.4 %), dry biomass (30.7 %), biological yield (17.5 %) and harvest index (17.7 %). This study demonstrates the substantial residual effects of AMF and Rhizobium inoculation on subsequent pigeon pea crops. The enhanced nutrient availability caused by these beneficial microorganisms' residual effects leads to increased plant growth and healthy biomass accumulation, ultimately improving grain yields in pigeon peas.